Integrated Functional High‐Strength Hydrogels with Metal‐Coordination Complexes and H‐Bonding Dual Physically Cross‐linked Networks. Issue 23 (12th August 2018) - Li, Xuefeng; Li, Rongzhe; Liu, Zuifang; Gao, Xiang; Long, Shijun; Zhang, Gaowen
Abstract: With the deepening of research on high‐strength hydrogels, the multi‐functional study of hydrogels has become a hot spot. In this paper, a dual cross‐linked physical high‐strength hydrogels is prepared by a relatively simple method. 2‐Vinyl‐ 4, 6‐Diamino‐2‐vinyl‐1, 3, 5‐triazine (VDT) induces the formation of the first cross‐linking points through the interaction of hydrogen bonds with poly(acrylamide‐co‐acrylic acid) (PAm‐co‐Ac) chains, then the secondary physical cross‐linkers Fe 3+ that introduce ionic coordinates between Fe 3+ and –COO − groups. Due to the synergistic effect of hydrogen bonding and ionic coordination, hydrogels possess high tensile strength (approx. 4.34 MPa), large elongation (approx. 17.64 times), and good healing properties under alkali solution after cutting into two pieces. Meanwhile, VDT contains diaminotriazine functional groups that easily form hydrogen bonds so that the polymer of hydrogels could absorb 5‐fluorouridine. In addition, the contribution of ionic polymer segments enables pH to be sensitive to hydrogels and facilitates the adsorption of a large number of ionic monomers to form ionic conductive networks, the prepared hydrogel capacitor device has very high sensitivity to pressure and deformation, and can detect the movement behavior of the human body. The dual‐physical cross‐linked hydrogels had a selective adsorption to biological small molecules and could be assembled into a flexible wearable device with high sensitivity. Abstract : Dual physical cross‐links of hydrogen‐bonding and ionic coordination significantly enhanced the hydrogel mechanical properties. Incorporation of VDT units into the copolymer chains endued the hydrogel with capacity of physical adsorption of antitumor 5‐fluorouridine, and ionic coordination provided good conductivity after absorbing Li + .